Relational mentorship for justice-oriented scholarship: space for care, reckoning, and supported discomfort. Issue 1 (2nd January 2023) - Lopez, Kimberly J.; Leighton, Jaylyn; Berbary, Lisbeth A.; Pirruccio, Michaela M.
ABSTRACT: We see relational mentorship as a move towards shared vulnerability, but also a relationship that is reciprocal, non-competitive, and non-authoritarian. We reflect on growth-spurring (and often uncomfortable) conversations about privilege, race, inaction, among other topics amidst social unrest and personal tensions with/in the systems in which we continue to be complicit. Through returning to cultural protocols, love, thinkacting, theorypracticing, and attentiveness to the affects of our full selves, we discuss the difficult and 'sacred' work of support one another's goals, celebrate milestones, and above all else, prioritize well-being above our individual or academic achievements in a neoliberal institution. We focus this paper on: (1) locating relational mentorship amongst existing approaches, (2) articulating relational mentorship and our experiences of it in relation to ongoing socio-political events, and (3) the ways relational mentorship can serve as a critique-in-practice of long-standing academic performances.